Policy maker and provider knowledge and attitudes regarding the provision of emergency contraceptive pills within Lao PDR - Sychareun, Vanphanom (BioMed Central, 2010)
BACKGROUND: The Ministry of Health (MOH) launched the National Reproductive Health Policy in 2005, which included recommendations regarding the use of emergency contraceptive pills (ECP). However, ECP have not yet been introduced officially in the public sector of the Lao PDR. Thus, their availability is limited. Understanding the knowledge of ECP and attitudes about their provision, barriers to use, and availability among health providers and policy makers is essential to successfully incorporate ECP into reproductive health services. METHODS: Qualitative research methods using in-depth interviews were employed to collect data from policy makers and health providers (auxiliary medical staff, nurses, and medical doctors). Altogether, 10 policy makers, 22 public providers, and 10 providers at private clinics were interviewed. Content analysis was applied to analyze the transcribed data. RESULTS: The majority of policy makers and health care providers had heard about ECP and supported their introduction in the public sector. However, their knowledge was poor, many expressed inconsistent attitudes, and their ability to meet the demand of potential users is limited. CONCLUSIONS: There is a need to train health providers and policy makers on emergency contraception and improve their knowledge about ECP, especially regarding the correct timing of use and the availability of methods. In addition, the general public must be informed of the attributes, side effects, and availability of ECP, and policy makers must facilitate the approval of ECP by the Lao Food and Drug Administration. These interventions could lead to increased access to and demand for ECP.